2006
DOI: 10.1523/jneurosci.1062-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Development of the Accumbens Relative to Orbitofrontal Cortex Might Underlie Risk-Taking Behavior in Adolescents

Abstract: Adolescence has been characterized by risk-taking behaviors that can lead to fatal outcomes. This study examined the neurobiological development of neural systems implicated in reward-seeking behaviors. Thirty-seven participants (7-29 years of age) were scanned using event-related functional magnetic resonance imaging and a paradigm that parametrically manipulated reward values. The results show exaggerated accumbens activity, relative to prefrontal activity in adolescents, compared with children and adults, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

89
1,095
7
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,113 publications
(1,206 citation statements)
references
References 67 publications
89
1,095
7
15
Order By: Relevance
“…The fact that many subcortical connections with the accumbens area had negative associations with age in both network types might be related to development of the reward center of the brain. The accumbens has been linked to risk‐taking behavior in adolescents (Galvan et al., 2006), but previous studies have not directly investigated the development of subcortical connection to the amygdala in children. Our results suggest that activity is increasingly directed by cortical regions rather than subcortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that many subcortical connections with the accumbens area had negative associations with age in both network types might be related to development of the reward center of the brain. The accumbens has been linked to risk‐taking behavior in adolescents (Galvan et al., 2006), but previous studies have not directly investigated the development of subcortical connection to the amygdala in children. Our results suggest that activity is increasingly directed by cortical regions rather than subcortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that adolescents suffer from a "reward deficiency syndrome," although intuitively appealing, is undermined by several studies that indicate elevated activity in subcortical regions, especially the accumbens, in response to reward during adolescence (Ernst et al, 2005;Galvan et al, 2006). An alternative account is that the increase in sensation-seeking in adolescence is due not to functional dopamine deficits but to a temporary loss of "buffering capacity" associated with the disappearance of dopamine autoreceptors in the prefrontal cortex that serve a regulatory negative-feedback function during childhood (Dumont et al, 2004, cited in Ernst & Spear, in press).…”
Section: Remodeling Of the Dopaminergic System At Pubertymentioning
confidence: 99%
“…Little is known about changes in reward seeking after adolescence, however, and there remain inconsistencies in the literature with respect to age differences in reward sensitivity after adolescence (cf. Bjork et al, 2004;Ernst et al, 2005;Galvan et al, 2006), likely due to methodological differences between studies in the manipulation of reward salience (e.g., whether the comparison of interest is in reward versus cost or among rewards of different magnitudes) and whether the task involves the anticipation or actual receipt of the reward. Nevertheless, studies of age differences in sensation seeking (in addition to our own) show a decrease in this tendency after age 16 (Zuckerman et al, 1978), and there is some behavioral evidence (Millstein & Halpern-Felsher, 2002) suggesting that adolescents may be more sensitive than adults to variation in rewards and comparably or even less sensitive to variation in costs, a pattern borne out in our Iowa Gambling Task data (Cauffman et al, 2007).…”
Section: Why Does Risk-taking Decline Between Adolescence and Adulthood?mentioning
confidence: 99%
“…This hypothesis is consistent with: (1) the frequent association between several manifestations of nonadherence and smoking and alcohol habits: for instance, smoking and excessive alcohol consumption are independent predictors of low practice of self-monitoring of blood glucose in diabetic patients [39]; (2) the effect of young age on non-adherence in chronic diseases [7]; (3) the frequency of non-adherence in teenagers (an experimental study showed that adolescents and people in their twenties have more difficulties in finding similarities between them now and them in the future than older people [40]); (4) the fact that the level of maturity is associated with adherence to immunosuppressive drugs in adolescent and young adults following heart transplantation [41]; (5) data from fMRI studies, providing the evidence that the balance between frontal and limbic circuitries is relatively late maturing during the brain development from childhood to adult age [42,43]: it is tempting (even if hazardous) to see an explanation of a risk in teenagers, not only for addiction, but also for poor adherence; (6) the effect of social deprivation on non-adherence to medication [44]: a shorter temporal horizon was found to be associated to a lower income [38]; (7) the effect of education on adherence to medication and other health behaviours [45]: a stronger future orientation of women, who asked more frequently for BRCA1/2 screening and mammography, was seen in women who had higher levels of education [35]; and finally (8), this explanation may represent a common link leading to a clustering of preventive behaviours in some individuals, this concept of 'healthy adherer' explaining the puzzling observation that adherence to a placebo is associated with a decrease in mortality [46].…”
Section: Discussionmentioning
confidence: 99%